INTERNATIONAL AND FOREIGN EXPERIENCE IN LEGAL REGULATION OF SOCIAL PROTECTION OF CHILDREN SUFFERED FROM THE MILITARY ACTIONS AND ARMED CONFLICTS - Beluga, Yulia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study and compare an experience of foreign countries in the legal regulation of social protection of children suffered from the military actions and armed conflicts and to identify the problems of regulatory support in this area of relations in the legislation of Ukraine. Research methods: comparative legal, formal logical and system analysis methods, structural and functional methods and other research methods. Results: analysing the legislation of Syria, Israel and Colombia on social benefits and guarantees for children suffered from the military actions, it could be noted that these countries have developed a number of special programmes and measures to support the most vulnerable segments of the population. For example, Syria’s experience in organising centres for the specialised psychological support and medical care could be very useful. Discussion: Ukraine should take into account the positive experience of other countries in legal regulation of social protection of children suffered from the war.